Studi Laju Korosi Baja Tahan Karat Martensitik 13CR Setelah Proses Perlakuan Panas [Effect of Heat Treatment of AISI 410 Martensitic Stainless Steel on Microstructure and Corrosion Resistance] - Dwisaputro, Rizky; Anwar, Mochammad Syaiful; Rusnaldy; Mabruri, Efendi (Jurnal Metalurgi, 2018)
Martensitic stainless steels are used in turbine blade materials in steam turbines of power plants. This study aims to determine the effect of heat treatment (austenitized and tempering) on microstructure and corrosion rate of AISI 410 martensitic stainless steel. The observation of microstructure was conducted using optical microscope and the corrosion test was performed in 3.5% NaCl solution which was carried out with Gamry G750 tool. The microstructure of AISI 410 steels after annealing process was composed of ferrite and metal carbide. The microstructure of martensite and retained austenite was obtained after the steel AISI 410 underwent a process of tempering at 600 °C with different austenitizing temperature. Meanwhile, the microstructure of temper martensite with retained austenite and metal carbide was found in AISI 410 steels after austenitized at 1050 °C with different tempering temperature. The corrosion rate of AISI 410 steels decreased with increasing austenitizing temperature. Meanwhile, very high corrosion current was found in AISI 410 steel at tempering of 550 °C and austenitized of 1050 °C.